Delineating a multi-element mineral deposit at Balatindi, Guinea, using geophysics - Amadu, Sulemana (University of Mines and Technology, 2019)
Balatindi Mineral Prospect, Guinea, is a multi-element mineral prospect that hosts Gold, Uranium and Copper with a potential for commercial production. It is located in eastern Guinea within the Bale` mylonitic zone, a zone of transition between the Archean Kenema-Man domain and Paleoproterozoic Birimian domain. A major challenge for exploration activities in the Balatindi area is the turnaround time for assay results due to the unavailability of a nearby assay laboratory. This coupled with the increasing cost of laboratory sample analysis calls for the need to find a faster and cheaper way of delineating mineral anomalies within the Balatindi area. Magnetic susceptibility and radiometric surveys are the two geophysical techniques applied to delineate gold and uranium anomalies respectively, because of the rapid and cost-effective ways in which data is acquired. Additionally, these methods yield substantial quantity of accurate data, thus enhancing interpretation and deduction. Downhole drill data for 37 HQ size diamond drilled holes of about 9200 m were used for the analysis. Magnetic susceptibility data were taken for 13 diamond drilled holes from the Central Polymetallic Prospect (CPP) area, whiles radiometric data were taken for the 24 drill holes in anomaly A to E areas. The data were correlated with the laboratory assay results for gold and uranium respectively. Strip logs comprising trace shades, histograms and line graphs, and statistics were used to interpret magnetic susceptibility readings against gold assay values, and radiometric readings against uranium assay values. Maximum and minimum values of -2.46 X 10-3 and 546.5 X 10-3 magnetic susceptibility were respectively recorded whiles 45 and 7250 cps were the maximum and minimum radiometric readings recorded. There was an inverse correlation between negative magnetic susceptibility values and gold assay values, however, there were few of such values to draw a definite conclusion. Positive magnetic susceptibility values did not show any preferential correlation with gold mineralisation. Radiometric count per second showed a very strong direct correlation with uranium mineralisation because it is a function of radiometric mineral present and therefore, radiometric survey can be used as a faster and cost-effective way of delineating uranium anomaly within the Balatindi prospect.
ix,93;ill.
Keywords: Multi-element mineral prospect; Minerals economy; Minerals industry; Minerals prospecting